Visual Function in Professional Drivers In A Coastal Town of South India and Their Perceptions About Ocular Health - Vidya Hegde; Rashmi Jain; Rashmi Shambu; Anupama Bappal; Rajarathna Hegde (Delhi Journal of Ophthalmology)
Introduction: Good visual function is essential for drivers during driving. Many ocular conditions affect visual function. There is a need for the drivers to undergo ocular evaluation and awareness about eye health would motivate them to do so. Aim: To assess vision acuity, field of vision, colour vision, contrast and depth perception of drivers and to assess their knowledge, attitude and practice about ocular health. Materials and methods: A cross sectional, descriptive study was done among drivers for duration of six months. (May to October 2016) After obtaining ethics committee approval & informed consent from participants, a detailed ocular evaluation was done. The drivers were given a validated semi-structured self-administered questionnaire that included demographic details and questions pertaining to awareness about ocular health. It was collected on same day. Descriptive statistics was used for analysis of data. Results: A total of 102 male drivers participated. The mean age of drivers was 36.19 years (SD ±14.50). Ocular findings observed included refractive errors (n=38), allergic conjunctivitis (n=23), pseudophakia (n=7), diabetic retinopathy (n=4), cataract, pterygium, strabismus and glaucomatous cupping (n=1 each). Vision impairment was seen in 19 drivers. Colour vision was normal in all. None of the drivers had undergone ocular examination at the time of issue or renewal of license or at the time of employment. Sixty drivers were aware that field of vision can be affected by eye diseases. Fifty seven drivers were not aware of about cataract and diabetic retinopathy affecting the vision. Conclusion: The study showed good visual function in drivers and they were less knowledgeable about cataract and diabetic retinopathy. They need to undergo periodic ocular evaluation.